1997
DOI: 10.1002/(sici)1099-1077(199711/12)12:6<557::aid-hup923>3.3.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

EEG, MAO‐A inhibition, pharmacokinetics and safety of befloxatone in the elderly

Abstract: Befloxatone is a new reversible and selective MAO‐A inhibitor. The present study aimed to assess the pharmacodynamics (EEG profile and MAO‐A inhibition using plasma levels of DHPG), pharmacokinetics and safety after a single dose of 10 mg of befloxatone compared to amitriptyline 50 mg in a randomized, double‐blind, three‐way crossover, placebo‐controlled trial involving 12 elderly subjects. Befloxatone did not show any sedative profile on EEG as no significant changes occurred in slow delta and theta waves or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The number of subjects was evaluated according to other studies using the same Methology/tests, evaluation, etc. [23,24].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The number of subjects was evaluated according to other studies using the same Methology/tests, evaluation, etc. [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, EEG modifications were found with nicardipine. This method is frequently used to assess the effects of psychotropic drugs [23,24] but apparently has never been applied to hypertensive patients, to evaluate the effects of antihypertensive drugs on cognitive functions. Nicardipine induces a psycho‐stimulant profile (decrease of slow delta waves and increase of alpha energy power).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, high doses of befloxatone also increased theta power, inconsistent with EEG profiles of smoking. Befloxatone has also been shown to increase beta power compared to placebo in elderly subjects (Patat et al, 1997). One interesting study examined the relationship between frontal midline theta activity and platelet MAO in healthy males (Hashimoto et al, 1988), and found a negative correlation between the two measures.…”
Section: Introductionmentioning
confidence: 99%